INCREASE THE EXPORT POTENTIAL OF UZBEKISTAN'S FRUIT AND VEGETABLE NETWORK - Mirxosilov Ulugbek Alisher o‘g‘li; Ashurmetova Nigora (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article explores strategies to enhance the export potential of Uzbekistan's fruit and vegetable industry. The study aims to analyze the current state of the agricultural network, identify key factors limiting export growth, and propose measures to strengthen the sector's competitiveness on global markets. The article highlights the importance of technological improvements, logistical optimization, and marketing strategies to boost Uzbekistan’s presence in international fruit and vegetable trade.